1995
DOI: 10.1007/bf01271469
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cognitive brain function and electrical brain activity in dementia of Alzheimer type

Abstract: Psychometric tests which assess cognitive brain function in dementia disorders are partly prone to artifacts, e.g., the experience of the investigator and the cooperation of the patient influences the results. An objective way to assess the degree of cognitive disturbance could be to measure neuronal activity represented by the electrical brain activity. The aim of the present study was to investigate how well cognitive function in dementia assessed by psychometric tests correlates with electrical brain activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
5
13
1
Order By: Relevance
“…General level of cognitive function, assessed in several previous studies with the MMSE, is most consistently related to alpha activity on EEG in AD patients [8,13,16,17,46], in agreement with our findings. However, also correlations between overall cognitive function and delta and theta activity were observed in our study and in previous reports [13][14][15][16].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…General level of cognitive function, assessed in several previous studies with the MMSE, is most consistently related to alpha activity on EEG in AD patients [8,13,16,17,46], in agreement with our findings. However, also correlations between overall cognitive function and delta and theta activity were observed in our study and in previous reports [13][14][15][16].…”
Section: Discussionsupporting
confidence: 82%
“…However, also correlations between overall cognitive function and delta and theta activity were observed in our study and in previous reports [13][14][15][16]. Our analysis of EEG activity in relation to domains of neuropsychological function showed that EEG abnormalities not only reflect a parietal lobe syndrome, as previously suggested [47], but that these disturbances are also closely related to frontal lobe functions.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Decreased EEG coherence and global field synchronization in α-band as well as frontal shift of generators of α-activity have been reported already in the MCI stage of AD supporting the hypothesis that AD develops as a neocortical disconnection syndrome [13,15,16,17]. Various EEG parameters were correlated in previous studies with measures of general cognition, neuropsychological test scores, clinical rating scales, regional cerebral blood flow and glucose metabolism as measured by SPECT and PET, respectively [13,18,19,20,21,22]. …”
Section: Introductionmentioning
confidence: 97%
“…Absolute delta and theta power in patients suffering from Alzheimer's disease is negatively correlated with cognitive function [14,15]. Furthermore, a positive correlation between cognitive performance and beta activity has been shown in patients suffering from Alzheimer's disease [16] as well as in nondemented elderly subjects [17].…”
Section: Introductionmentioning
confidence: 99%